Willingness for cervical cancer screening and associated factors among HIV positive women on follow-up at Jinka General Hospital, Southern Ethiopia. - Gebeyehu, Selamawit; Tura, Gurmesa; Admassu, Bitiya (Ethiopian Journal of Reproductive Health, 2021)
Background: Cervical cancer is one of the leading causes of death in women worldwide. Women living with Human Immunodeficiency virus are at higher risk of acquire cervical cancer. Despite the importance of screening, the proportion of willingness for screening among these women is low in Ethiopia. Therefore, this study aimed to determine the magnitude of willingness for cervical cancer screening and its associated factors among women living with HIV. Methods: A facility-based cross-sectional study was conducted from March 14 to May 8, 2018.341 women were selected by using systematic sampling method among adult HIV positive women attending treatment at Jinka general hospital. The data were collected using an interviewer-administered questionnaire. Bivariate and multivariable logistic regression analyses were used to determine the presence and the strength of association between dependent and independent variables by using odds ratio with 95% confidence interval. Results: The status of willingness for cervical cancer screening was 56.9% (95%CI; 51.6%, 62.1%). Women aged 40 years and above (AOR=2.58; 95% CI = 1.21-5.45), having two or less number of children (AOR=2.49; 95% CI =1.3-4.78), having awareness about cervical cancer screening (AOR = 4.85; 95% CI = 2.56-9.17), high perceived susceptibility (AOR=5.02;95%CI=2.74-9.18) and low perceived barrier (AOR=9.87; 95% CI = 5.34-18.31) were found to increase willingness for cervical cancer screening. Conclusions: In this study, the willingness for cervical cancer screening among HIV positive women was low. Age, number of living children, awareness about cervical cancer screening, perceived barrier and susceptibility were independent factors associated with the willingness of cervical cancer screening. Health care workers and cervical cancer prevention and control programs should create awareness by using different mass media. Health care providers should counsel on the above barrier for willingness to cervical cancer screening.